Silencing of the HER2/neu Gene by siRNA Inhibits Proliferation and Induces Apoptosis in HER2/neu-Overexpressing Breast Cancer Cells - Faltus, Timo (Neoplasia Press Inc., 2004)
In eukaryotes, double-stranded (ds) RNA induces sequence-specific inhibition of gene expression referred to as RNA interference (RNAi). We exploited RNAi to define the role of HER2/neu in the neoplastic proliferation of human breast cancer cells. We transfected SK-BR-3, BT-474, MCF-7, and MDA-MB-468 breast cancer cells with short interfering RNA (siRNA) targeted against human HER2/neu and analyzed the specific inhibition of HER2/neu expression by Northern and Western blots. Transfection with HER2/neu-specific siRNA resulted in a sequence-specific decrease in HER2/neu mRNA and protein levels. Moreover, transfection with HER2/neu siRNA caused cell cycle arrest at G(0)/G(1) in the breast cancer cell lines SKBR-3 and BT-474, consistent with a powerful RNA silencing effect. siRNA treatment resulted in an antiproliferative and apoptotic response in cells overexpressing HER2/neu, but had no influence in cells with almost no expression of HER2/neu proteins like MDA-MB-468 cells. These data indicate that HER2/neu function is essential for the proliferation of HER2/neu-overexpressing breast cancer cells. Our observations suggest that siRNA targeted against human HER2/neu may be valuable tools as antiproliferative agents that display activity against neoplastic cells at very low doses.